Fast Track The Factors of Sustainable Management of Aquatic Animals in Samphan District, Phongsaly Province - vongchit, yi; MANYSIRD, Yeechit (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
The Factors of Sustainable Management of Aquatic Animals in Samphan District, Phongsaly Province Yeechit MANYSIRD, Sangkhom INTHAPAN and Khamkeo NAOYENG Faculty of Agriculture and Forest Resources, Souphanouvong University Tel: +856 20 51540001, E-mail: ychmanysurt@gmail.com Abstract This study examined the factors affecting sustainable aquatic resource management in Samphan District, Phongsaly Province, Lao PDR. The objectives were to investigate the current status of aquatic resource management, identify the factors influencing management practices, and propose guidelines for the sustainable conservation of aquatic resources. The study was conducted in three villages: Had Nga Nua Village, Na Village, and Yang Nua Village. Data collection and writing the report were carried out from June 2025 to May 2026. A mixed-methods research approach was employed, utilising questionnaire surveys, interviews with community leaders, and consultations with relevant local authorities. The collected data were analysed using descriptive statistics, including frequency and percentage, as well as content analysis. The findings revealed that community participation in aquatic resource management was at a moderate to high level. Local communities actively organised patrols and cooperated in managing water resources. However, the enforcement of village regulations remained at a moderate level due to occasional violations. Access to information and participation in training activities were rated highly, mainly because of support from various development projects. Regarding factors affecting aquatic resource management, the decline in fish species was identified as the most significant concern, cited by 88% of respondents. Other important factors included community participation (85%), the impacts of dams and changes in aquatic habitats (81%), enforcement of village regulations (78%), the use of inappropriate fishing gear (76%), access to information (72%), climate change (69%), and insufficient management budgets (64%), respectively. The study also examined changes in fish species diversity between 2020 and 2024. The results showed that the rate of decline in fish species increased continuously from 5% in 2020 to 8% in 2021, 15% in 2022, 22% in 2023, and 30% in 2024. In contrast, the rates of increase in fish species were only 2%, 3%, 1%, 0.5%, and 0.2%, respectively. These findings indicate a worrying decline in aquatic biodiversity. Community income was found to fluctuate according to production conditions. The average annual income was 14,400,000 Kip in 2020, decreasing to 13,800,000 Kip in 2021, representing a decline of 4.1%. Income then increased to 16,800,000 Kip in 2022 (21.7% increase) and 18,600,000 Kip in 2023 (10.7% increase). However, it declined to 17,400,000 Kip in 2024, a decrease of 6.4%, primarily due to the significant reduction in natural fish stocks. In conclusion, sustainable aquatic resource management in Samphan District, Phongsaly Province, continues to face numerous challenges, particularly the decline in fish species, the impacts of water resource development, and the overexploitation of aquatic resources beyond their natural recovery capacity. Therefore, strengthening community participation, improving regulatory enforcement mechanisms, promoting fish habitat restoration, and creating alternative livelihood opportunities for local communities are essential measures to ensure the long-term sustainability of aquatic resource management. Keywords: aquatic resource management, community participation, fish species diversity, influencing factors, sustainability